Uma abordagem para detecção de pessoas em imagens de veículos aéreos não-tripulados - Oliveira, Diulhio Candido de (2016)
This work aims to propose a method for people recognition in Small Unmanned Aerial Vehicles aerial imagery. This is an application of high interest, it can be used in several situations, both civilian and military, as search and rescue missions. The use of Unmanned Aerial Vehicles autonomously tends to increase with the cheapening of this technology, supporting search and rescue missions. Thus, this technology can excel over others currently used, as satellites and flights with large aircraft. For autonomous people recognition, this work proposes new methods as Pattern Reconigition System (PRS) applied to image recognition, applying it in aerial images. Four Pattern Reconigition techniques were tested: Convolutional Neural Networks, HOG+SVM, Haar Cascade and LBP Cascade. Furthermore, in order to achieve recognition of people in aerial images in Real-Time target and detection techniques were tested and evaluated: Saliency Maps and Low-resolution Thermal Image Processing (TIP). In this work were considered recognition rates of the methods and their computational time in a low-cost embedded system and a Mobile Ground Control Station (MGCS). The recognition results shown the Convolutional Neural Network potential, where an accuracy of 0.9971 was achieved, followed by HOG + SVM with 0.9236, Haar Cascade with 0.7348 and LBP Cascade with 0.6615. In situations simulated partial occlusion, where was the CNNs achieved average Sensitivity of 0.72, HOG+SVM with 0.50 and both Cascades 0.20. In experiments with PRS (targeting and detection algorithms with the recognition techniques), the Saliency Map had little influence in recongition rates, it was close to the rates achieved in recognition experiments. While the Low-resolution Thermal Image Processing had difficulties in segmentation process, where translation variantions occured, it harmed the system precision. Lastly, this work proposes a new approach for PRS implementation for people recognition in aerial imagery, using TIP with CNN. This PRS combines high rates of recognition with an computational performace of, at least, 1 fps in MGCS plataform.